Metagenomic analysis of microbial consortium GF-20 in corn stover degradation at low temperature - Bi-zhou Zhang; Qinggeer Borjigin; Ju-lin Gao; Xiao-fang Yu; Shu-ping Hu; Fu-gui Wang; Xin Zhang; Sheng-cai Han (Journal of Environmental Engineering and Landscape Management, 2023)
In our previous work, a microbial consortium GF-20 (Qinggeer et al., 2016) was enriched from compost habitats and adapted to efficiently and stably degrade corn stover under low temperatures. While the main microorganism and degradation-related functions and degradation-related coding enzyme genes of GF-20 were not clear. Therefore, the current study used the metagenomic to decipher the systematic and functional contexts within such microbial consortium under low temperatures. The results showed that the dominant functional microbials in GF-20 consortium were bacteria. The dominant phylums in GF-20 consortium were Proteobacteria (62.84%) and Bacteroidetes (10.24%). The dominant genus was Pseudomonas (50.84%), followed by Dysgonomonas (5.86%), Achromobacter (4.94%), Stenotrophomonas (3.67%) and Flavobacterium (2.04%). The metabolism was mainly composed of carbohydrate metabolism and amino acid metabolism, and included signal transduction, cell transport and other metabolic modes. The functional genes encoded were mainly distributed in glycosidolytic enzyme genes, and the functional enzymes were β-glucosidase, acetyl-CoA, pyruvate dehydrogenase and galactosidase. The GF-20 microbial consortium degraded the cellulose in corn stover primarily by β-glucosidase and endoglucanase, which were produced by 12 genera of microorganisms. The hemicellulose synergistic effect was produced by 15 genera of microorganisms including xylanase, xyloglucanase, mannolanase and branching enzyme.